A precut column design and control using ASPEN - Nor Syazwani, Sukri (2008)
Pre-cut column from the Palm Oil Fractionation Plant is one approach to the distillation of fatty acids. This research aim to develop dynamic Pre Cut Column model using ASPEN and incorporate control system into distillation column model. The scope of this study is to learn how to use dynamic simulators by simulating Pre Cut Column in steady-state condition and moving to a dynamic simulation, then applying PID (proportional-integral-derivative) control system as an effective control system for continuous processes. For designing the precut column, the method that must be concerned are specifying chemical components and physical properties, specifying stream properties and specifying equipment parameters before running the simulation. PID controllers are the controller of choice for controlling the precut column because PID system is a balancing act with all terms interacting. Integral feedback Element (I) is added to the proportional element to provide a means for eliminating a changing offset in a non linear system and to slow down the reaction to allow for the time delays in the system. Derivative feedback element (D) is added to provide a means of reducing sudden changes in the output and will provide a faster response to step functions and transients. The result was in steady state simulation of precut column and the parameters of controllers were identified from dynamic responses. Dynamic simulation has become increasingly important as processes become more complex and are designed and operated closer to constraints.